33 OHCA and COPD, incidence, outcome and seasonal variation. (26th April 2019) - Braagaard, Lone; Jensen, Theo W; Holgersen, Mathias G; Blomberg, SN; Lippert, Freddy; Christensen, Helle C
Abstract : Background: In Denmark, 30 day survival from OHCA have tripled from 2001–2011, but not among COPD patients. It is known that COPD patients are less likely to have; witnessed arrest, bystander actions and a shockable rhythm. The purpose of this study is to present updated rates of incident, survival to hospital, EMS treatment and seasonal variation among OHCA in COPD patients. Method: Data was collected from the verified 2016 Danish OHCA of patients with history of COPD noted in the EMS records. Incidence rates per 100.000 inhabitants, survival rates to hospital and EMS resuscitation attempt are presented. Fisher's exact and Chi-square test was used to assess significant differences in survival rates between COPD and non-COPD OHCA victims. Monthly variations of OHCA in COPD patients are presented as percentages. Results: In 2016 there were 1480 indexed and verified OHCA in the capital region of Denmark. Preliminary data show OHCA incidence rates in COPD patients is 8.4 per 100.000 inhabitants, survival to hospital rates of 29.1%, and a seasonal variance with high incidences in winter months (range: 4% in April – 13.9% in November). There was a significant difference in termination of treatment prior to arrival at hospital (COPD: 69.5%; non-COPD: 59.6% p:0.004). Conclusion: Preliminary data show that COPD patients still have a significant worse outcome. The reported seasonal variance and incidence rates can aid campaigns to improve survival. Data extraction and analysis on treatment prior to arrest and clearing of confounding factors might lead to more effective campaigns to improve survival. Reference: Moeller, S.G. et al . Temporal trends in survival after out-of-hospital cardiac arrest in patients with and without underlying chronic obstructive pulmonary disease. Resuscitation 104 (2016) 76–82. Karlsson, L.I.M. et al . Diurnal variations in incidence and outcome of out-of-hospital cardiac arrest including prior comorbidity and pharmacotherapy: A nationwide study in Denmark. Resuscitation 85 (2014) 1161–1168. Conflict of interest: None. Funding: None.